(untitled) (Південний архів (історичні науки), 2025)
The purpose of the article is to highlight the transformational processes in the sphere of culture and art caused by the Revolution of Dignity and to highlight the need to realize the scale of these transformations during the revolution and their significance for Ukrainian society. The research methodology is based on the application of general scientific and special methods of cognition, in particular, a systemic approach, analysis, synthesis, logical method, and method of visualization of research results. The results of the work consist in determining the nature of the transformational processes in the sphere of culture and art caused by the Revolution of Dignity and in generalizing the views of scientists regarding their role in the revolutionary processes and their significance for Ukrainian society.The genetic connection of the events of the Revolution of Dignity with the direction of further socio-cultural development of Ukraine, awareness of the future in which the next generation will have to live, which is an urgent task of further scientific research, has been established and clarified. Conclusions. The identification and highlighting of specific cultural and artistic manifestations brought by the Revolution of Dignity, namely: in journalism and literature, poetry, Ukrainian song, music, in all forms and genres of fine art, poster graphics, photography, art installation, performance, cinema, museum art, etc. showed that they had a significant impact on the course of the revolution and on post-revolutionary changes in Ukrainian society, and activated the development of all spheres of culture and art.After the victory of the revolution, in the post-Maidan period, these transformations provided prospects for the further development of culture and art. Despite the wide range of reflection in historiographic sources of the course and problems of the Revolution of Dignity, in our opinion, the transformational processes in the sphere of culture brought by the revolution, given their significance and scale, require comprehensive understanding, research, and preservation in historical memory.